The Relationship Between Self-Concept and Anxiety with Adjustment Among First-Year Migrant Students - Jamaah Mundaroh; Kholifah Umi Sholihah (Journal of Educational Sciences, 2026)
First-year migrant students often face psychological and social challenges when adapting to a new academic and social environment. Internal factors such as self-concept and anxiety play an important role in determining students’ ability to adjust effectively. his study aims to examine the relationship between self-concept and anxiety with self-adjustment among first-year migrant students. This study employed a quantitative correlational design. The participants were 83 first-year migrant students aged 18–25 years, selected using a quota sampling technique. Data were collected using self-concept, anxiety, and self-adjustment scales measured with a four-point Likert scale. Data analysis was conducted using multiple linear regression analysis. The results showed a significant relationship between self-concept and anxiety with self-adjustment (r = 0.730; p < 0.01), with an effective contribution of 53.3%. Self-concept had a significant positive relationship with self-adjustment (r = 0.651; p < 0.01), while anxiety had a significant negative relationship with self-adjustment (r = -0.686; p < 0.01). Self-concept and anxiety are significant predictors of self-adjustment among first-year migrant students. Strengthening positive self-concept and managing anxiety are essential to support successful adjustment in the university environment.